Customer Relationship Management in the Organization of Pilgrimage Tourism to the Jasna Góra Monastery - Izabella SOWIER-KASPRZYK (Communications of International Proceedings, 2021)
Purpose: The aim of the paper was to present the results of the research concerning the value of using one of the forms of partnership marketing which is customer relationship management. The unique nature of the article is that customer relationship management is about pilgrimage tourism. The research allowed the author to investigate the subject of the management of relations with pilgrims going on a pilgrimage on foot to Jasna Gora Monastery in Czestochowa, Poland. Moreover, attention was paid to the role of feelings, knowledge and activities in managing customer relations. Design/Methodology/Approach: The research methodology is based on pilgrim surveys and expert interviews. and a confrontation with the latest research literature. In addition, a literature analysis of the study of this phenomenon was carried out. Findings: The study showed that creating, maintaining and managing customer relationships definitely has applications in pilgrimage tourism. The time before, during and after the pilgrimage is conducive to building, strengthening and maintaining long-lasting relationships. Pilgrims expect individualized contact with the organizing priests, based on religious feelings. Moreover, pilgrimage tourism is characterized by high emotional involvement in relationships with pilgrim clients, and the relationship based on religious feelings and spirituality is permanent. The organizers should use these opportunities to manage relations with pilgrims and the value of these relations is mutual. Practical Implications: The research results deepen the knowledge related to the subject of partnership marketing in pilgrimage tourism. They can be used in the implication of specific solutions in managing relations with pilgrims by organizers, in particular priests. Additionally, the application of the proposed activities may have a positive impact on the development of the pilgrimage movement. Originality/Value: The application of the solutions proposed in the article influences the development of knowledge in managing relations with pilgrims. The article may be useful for organizers of pilgrimages, as well as for managers of pilgrimage centres. In addition, the use of appropriate relationship management solutions may have a direct impact on the development of pilgrimage centres.
Keywords: customer relationship management; pilgrimage tourism; partnership marketing; management